Book review: Forgotten things: the story of the Seymour Valley Archaeology Project by Robert Muckle - Pecknold, Colleen (My University, 2026)
Forgotten Things: The Story of the Seymour Valley Archaeology Project highlights the importance of sharing the knowledge resulting from archaeological excavation and analysis. The book disseminates not only the methods used in archaeology but also clearly distinguishes what was discovered during excavation and how artifacts were interpreted. Because one of the main goals of the Seymour Valley project field school was education, Robert Muckle outlines a teaching approach that demonstrates ethical behaviour, training the next generation of archaeologists to avoid recreating and reinforcing discriminatory, exclusionary and unsafe practices. I would recommend this book for anyone who is seeking to learn about archaeological field work and excavations, and also for anyone who wants to learn about the early 20th century history of the Lower Seymour Valley in British Columbia. It's an engaging, accessible read with clear language combined with plenty of maps and drawings to help situate the story of people of the past within this specific archaeological site.
Keywords: Forgotten Thing: The Story of the Seymour Valley Archaeology Project; archaeology; ethical behaviour; book review; British Columbia